Correlation of TPO Antibody Concentration with Thyroid Hormones as a Predictor of Clinical Hypothyroidism - Mila Vasilj-Mihaljević; Ivan Mihaljević; Sanja Bekić; Željko Zubčić; Ana Vasilj; Danijela Daus-Šebeđak; Ivana Škrlec; Jasminka Talapko (Acta Clinica Croatica, 2024)
This study aimed to determine the relationship between the concentration of thyroid peroxidase antibodies (TPO-Ab) and thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3) in patients with chronic lymphocytic thyroiditis. This cross-sectional study included 144 patients diagnosed with chronic lymphocytic thyroiditis whose mean age was 46±15 years at the time of diagnosis. According to their TSH concentration, the patients were either euthyroid or hypothyroid. After 59 patients were excluded due to TSH levels below the reference range, no TPO-Ab findings, substitution therapy, immune hyperthyroidism, or TPO-Ab and TSH levels outside the resolution limits of the laboratory tests, 85 patients remained in the study. A positive correlation was found between TPO-Ab and TSH concentration within the euthyroid and hypothyroid range and a negative correlation between TPO-Ab and FT4 concentration. The result suggests that the TSH and TPO-Ab concentration could be used to identify individuals at risk for the development of hypothyroidism in the general population.